Chad : First Review Under the Extended Credit Facility Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Request for Modification of Performance Criteria, and Augmentation of Access. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Chad's First Review Under the Extended Credit Facility (ECF) Arrangement, Request for Waivers of Nonobservance of Performance Criteria (PC), and Request for Modification of PC, and Augmentation of Access. Performance under the ECF supported program was broadly satisfactory in 2014, with four of six quantitative PCs observed as of end-December, and sustained implementation of the structural reform agenda. The authorities have adopted decisive measures to address large oil revenue shortfalls and close the external financing gap, particularly through a significant fiscal adjustment in 2015 and beyond. The IMF staff supports the completion of the first review under the ECF arrangement.